CEPF Western Ghats Special Series: Anurans of the Meghamalai landscape, Western Ghats, India - G. Srinivas; S. Bhupathy (Journal of Threatened Taxa, 2013)
Meghamalai landscape, southern Western Ghats was surveyed for anurans from March 2006 to January 2009. Including published data, a total of 35 species of anurans belonging to 19 genera and eight families have been reported from the area. This includes 23 (65.7%) species endemic to the Western Ghats. New locality records for four species namely, Fejervarya mudduraja, Raorchestes griet, R. ponmudi and Rhacophorus pseudomalabaricus were obtained. Several species recorded from the area are listed under various threat categories of IUCN Red List. Further studies are required to understand the ecological requirements of the anurans of the landscape.